Molecular hybridization modification improves the stability and immunomodulatory activity of TP5 peptide - Wang, Junyong; Tang, Yuan; Zhao, Xuelian; Ding, Zetao; Ahmat, Marhaba; Si, Dayong; Zhang, Rijun; Wei, Xubiao (Frontiers in Immunology, 2024)
Thymopentin (TP5) plays an important role in host immunomodulation, yet its bioavailability is significantly limited by its short half-life. YW12D is a peptide with strong stability but relatively weak immunoactivity. Tuning the physicochemical properties of such molecules may yield synthetic molecules displaying optimal stability, safety and enhanced immunological activity. Here, natural peptides were modified to improve their activity by hybridization strategies. A hybrid peptide YW12D-TP5 (YTP) that combines TP5 and YW12D is designed. The half-life of YTP in plasma is significantly longer than that of YW12D and TP5. YTP also displays an improved ability to protect the host from CTX-induced weight loss and thymus and spleen indices decrease than YW12D and TP5. In addition, YTP promotes dendritic cell maturation and increases the expression of cytokines IL-1β, IL-6, TNF-α and immunoglobulins IgA, IgG, and IgM. A combination of antibody-specific blocking assay, SPR, molecular dynamics simulations and western blotting suggest that the immunomodulatory effect of YTP is associated with its activation of the TLR2-NF-кB signaling axis. In sum, we demonstrate that peptide hybridization is an effective strategy for redirecting biological activity to generate novel bioactive molecules with desired properties.